What Can We Quantify About Carer Behavior? - Savage, James L.; Hinde, Camilla A. (Frontiers in Ecology and Evolution, 2019)
In many species, individuals must contribute extensively to offspring care to reproduce successfully. Within species, variation in care is driven by local social, physiological, and environmental contexts, and this relationship has been a major focus of behavioral ecology since the inception of the field. The majority of existing studies on care, both theoretical and empirical, have focused on measuring the amount of care delivered by each carer as a proxy for individual investment, linking this investment to the local context, and investigating outcomes for offspring. However, more recently interest has grown in the finer-scale details of care, including how individuals respond to each other’s behavior, and temporal variation in care both within and between stages. Simultaneously, advances in remote monitoring methods, such as video cameras and passive integrated transponder (PIT) tag systems, have vastly increased the ease of collecting large amounts of care data, providing opportunities to study carer behavior in much greater detail than previously possible. In this mini-review we provide an overview of the dimensions of carer behavior that can be quantified, illustrated using recent studies from a variety of taxa. We classify these analyses into three broad groups: (a) how parental care is distributed in time, (b) variation within care events, and (c) how carers interact when jointly providing care. Our aim is to encourage more in-depth analyses of parental care, to build a more complete picture of how animals rear their offspring.